American Headache Society Survey About Urgent and Emergency Management of Headache Patients. Issue 9 (12th September 2018) - Minen, Mia T.; Ortega, Emma; Lipton, Richard B.; Cowan, Robert
Abstract: Background: Emergency department (ED) visits for migraine are burdensome to patients and to the larger healthcare system and society. Thus, it is important to determine strategies used to prevent ED visits and the common communication patterns between headache specialists and the ED team. Objective: We sought to understand: (1) Whether headache specialists use headache management protocols. (2) The strategies they use to try and reduce the number of ED visits for headache. (3) Whether protocols are used in the EDs with which they are affiliated. (4) The level of satisfaction with the coordination of care between headache physicians and the ED. Methods: We surveyed via SurveyMonkey members of the American Headache Society Emergency Department/Refractory/Inpatient (EDRI) Section to understand their practice regarding patients who call their office to be seen urgently, and to understand their communication with their local EDs. Results: There were 96 eligible AHS members, 50 of whom responded to questionnaires either by email or in person (52%). Of these, 59% of respondents reported giving rescue treatment to their patients to manage acute attacks. Fifty‐four percent reported using standard protocols for outpatients not responding to usual acute treatments. In the event of a request for urgent care, 12% of specialists reported bringing patients into the office most or all of the time, and 20% reported sending patients to the ED some or most of the time for headache management. Thirty‐six percent reported prescribing a new medicine and 30% reported providing telephone counseling some/most/all of the time. Sixty percent reported that their ED has a protocol for migraine management. Overall, 38% were usually or very satisfied with the headache care in the ED. Conclusions: A substantial number of headache specialists are dissatisfied with the care their patients receive in the ED. More standardized protocols for ED visits by patients with known headache disorders, and clear guidelines for communication between ED providers and treating physicians, along with better methods for follow‐up following discharge from the ED, might appear to improve this issue.